Farmers' Work Time Allocation in Rice Paddy Farming in Sindo Makmur Village, Tiworo Islands Sub-district West Muna Regency - Arfan, Arfan; Bahari, Bahari; Ilma Sarimustaqiyma Rianse (International Journal of Technology and Education Research, 2025)
The objectives of this research are 1) to examine farmers' efforts in allocating work time in lowland rice farming activities and other farming activities, 2) to analyze how much income from lowland rice farming is obtained by farmers in Sindo Makmur Village, Toworo Islands District, West Muna Regency. This research will be carried out in August 2022. The object of this research is the Allocation of Farmers' Working Time in Rice Farming. The method used is the case study method. The analysis used is descriptive analysis and income analysis. The results of the research show that the Allocation of Farmers' Working Time in Lowland Paddy Farming Activities and Non-Paddy Rice Farming Activities of Sindo Makmur Village, Tiworo District, West Muna Regency shows that lowland rice farming is a priority activity for farmers while cucumber growing is a side farming activity for farmers. This is to utilize farmers' free time and side income outside of rice farming activities. in this way, farmers divide their working time between lowland rice farming and cucumber farming. Meanwhile for knowing the allocation of farmers' working time in lowland rice farming requires 525 hours during one season. Meanwhile, cucumber plants only need less time, around 189 hours. Meanwhile, the average income from rice farming in Sindo Makmur Village, Tiworo Islands District, West Muna Regency in one harvest is IDR 7,846,703/hectare